A Facile Preparation of Ambient Pressure–Dried Hydrophilic Silica Aerogels and Their Application in Aqueous Dye Removal - Yang, Xianghua; Wu, Zhixu; Chen, Haifeng; Du, Qixuan; Yu, Lin; Zhang, Ruiyang; Zhou, Ying (Frontiers in Materials, 2020)
Highly porous hydrophilic silica aerogels (SAs) are potential excellent adsorbents in aqueous media, which are generally synthesized via a standard sol–gel method followed by the relatively complex and dangerous supercritical fluid drying process. Herein, a facile and novel synthetic method applying ambient pressure drying technology for the rapid preparation of hydrophilic SAs is reported, which are soaked by metal cations without the need of traditional surface modification and supercritical fluid drying process. Chemical and physical properties of the hydrophilic SAs were characterized and compared with a trimethylchlorosilane (TMCS) modified hydrophobic silica aerogel. Besides the integrity and low shrinkage of the as-prepared products, Fourier transform infrared (FTIR) spectra and integrated thermal analyzer (ITA) results revealed the presence of hydroxyl groups as well as the absence of multitudinous hydrophobic groups on the silica surface after soaking. Field emission scanning electron microscope (FE-SEM) and Brunauer–Emmett–Teller (BET) measurements confirmed the mesopores inside the aerogel skeleton. Among the tested metal cations, the Mg2+ soaked SAs demonstrated the best pore properties (pore diameter 9.35 nm and pore volume 1.09 cc/g) while the Fe3+ soaked ones got the biggest surface area (855.62 m2/g) in contrast to other metal cations. Rhodamine B and Methylene blue solutions are used to check the absorption ability of the SAs in aqueous media, where the best adsorption capacity for Rhodamine B and Methylene blue reached 2.8 mg/g and 40.4 mg/g, respectively, showing a potential application in aqueous pollutant removal.